Transport of MHD couple stress fluid through peristalsis in a porous medium under the influence of heat transfer and slip effects - Sankad, G.C.; Nagathan, Pratima S. (Zielona Góra: Uniwersytet Zielonogórski)
An attempt has been made to examine the effects of magnetohydrodynamic couple stress fluid in peristaltic flow with porous medium under the impact of slip, heat transfer and wall properties. The expressions are obtained for temperature, coefficient of heat transfer and velocity. Influences of different parameters, the Hartmann number, Brinkman number and adaptability parameters on the temperature and warmth trade coefficient are discussed through outlines.
Keywords: peristaltic flow; couple stress fluid; Darcy number; slip parameter; compliant walls